Acknowledging User Requirements for Accuracy in Computational Chemistry Benchmarks. Issue 14 (22nd April 2020) - Savin, Andreas; Pernot, Pascal
Abstract : Computational chemistry has become an important complement to experimental measurements. In order to choose among the multitude of the existing approximations, it is common to use benchmark data sets, and to issue recommendations based on numbers such as mean absolute errors. We argue, using as an example bandgaps calculated with density functional approximations, that a more careful study of the benchmark data is needed, stressing that the user's requirements play a role in the choice of an appropriate method. We also appeal to those who measure data capable of being used as a reference, to publish error estimates. We show how the latter can affect the judgment of approximations used in computational chemistry. Abstract :